Efficacy and safety of regorafenib compared to placebo and to post-cross-over regorafenib in advanced non-adipocytic soft tissue sarcoma. (August 2018) - Brodowicz, Thomas; Mir, Olivier; Wallet, Jennifer; Italiano, Antoine; Blay, Jean-Yves; Bertucci, François; Eisterer, Wolfgang; Chevreau, Christine; Piperno-Neumann, Sophie; Bompas, Emmanuelle; Ryckewaert, Thomas; Liegl-Antzwager, Bernadette; et al.
Abstract: Introduction: The placebo-controlled phase-2 REGOSARC trial demonstrated the efficacy of regorafenib in patients with leiomyosarcoma, synovial sarcoma and other non-adipocytic sarcoma but not in liposarcoma. Patients initially allocated to placebo were allowed to receive regorafenib after progression. We report here an updated analysis of the trial including evaluation of regorafenib activity after cross-over. Methods: From June 2013 to December 2014, 139 patients were enrolled in the non-adipocytic sarcoma cohorts. Median follow-up is now 32.4 months. Benefit of regorafenib versus placebo in terms of progression-free survival (PFS) and overall survival (OS) from randomisation was estimated by hazard ratio (HR) in Cox models. In the placebo arm, intra-patient benefit of regorafenib after cross-over was evaluated by the growth modulation index (GMI) (GMI was here, for each patient, PFS after cross-over regorafenib divided by PFS with placebo). Furthermore, the activity of delayed (after cross-over) versus early (at study entry) regorafenib was evaluated by comparing PFS after cross-over to regorafenib to PFS after randomisation in the regorafenib arm. Results: PFS benefit of regorafenib as compared to placebo was confirmed with longer follow-up (HR = 0.50; 95% CI: 0.35–0.71; p < .0001). OS was not statistically significant different (HR = 0.78; 0.54–1.12; p = .18). This finding may partially be explained by the fact that 55/68 patients who progressed on placebo (81%) received cross-over Regorafenib after progression: 59% of them had a GMI ≥ 1.3 (95% CI, 45–71%). Delayed start of regorafenib was associated with a statistically non-significant shorter PFS as compared to early treatment (HR = 1.21; 0.84–1.73; p = .30) without impact on OS. Conclusions: Observed PFS confirms that regorafenib warrants further clinical investigation in refractory non-adipocytic sarcomas. Highlights: Regorafenib improves progression-free survival in pretreated non-adipocytic sarcoma as compared to placebo. Regorafenib slows down tumour growth in 59% of cross-over patients. After exposure placebo and cross-over, regorafenib is an active drug in non-adipocytic sarcomas.